SISTEM PENGAWASAN DPRD TERHADAP PEMERINTAH DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN KONAWE - , Dewi Fitriany Tondra, S.Ip ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to provide a description on how the Parliament of Konawe in period 2004-2009 conducted oversight on local government in an increase of Konaweâs local revenues. Creative purpose is to know the efforts made and the constraints that affect the implementation of the oversight function of Konawe Parliament on the implementation of Local Regulations and policies of local governments to increase local revenues in Konawe. Innovative purposes are to be able to find, appoint and provide alternative ideas as well as legal efforts that can be used to optimize the role of Parliament Konawe to increase revenue and achieve good governance. This study combines the methods of juridical normative and sociological research done by way of inventory data and conducting interviews to the respondents and then analyzing by qualitative descriptive analysis. Form of data in this study includes primary data, secondary data and tertiary data. This study was conducted in Southeast Sulawesi Province Konawe at the Regional Representatives Council and Local Government Konawe. Based on research results, the oversight system of Konawe Parliament toward local government in raising revenue as stipulated in the Code of Parliament and is only concerned with financial accountability of local government which is reported at each end of office term of the Regent. Legal constraints faced by the Parliament in overseeing that there are no further instructions or technical instructions regarding the procedure of supervision meant that supervision is carried out based on their own interpretation. Legal steps taken by Parliament is to maximize the role of parliament as a watchdog of local government by accepting, following up on public statements and aspirations of the people that came in, improving coordination among agencies and related agencies, to maximize the role of mass media and nongovernmental organizations as partners of local government expected to be a control for local governments to improve services and to give legal protection to the community thus contributing to the increasing of revenue of Konawe Regency.